Knockout of tnni1b in zebrafish causes defects in atrioventricular valve development via the inhibition of the myocardial wnt signaling pathway. Issue 1 (25th July 2018) - Cai, Chen; Sang, Caijun; Du, Juan; Jia, Haibo; Tu, Jiayi; Wan, Qing; Bao, Binghao; Xie, Shanglun; Huang, Ying; Li, Ao; Li, Jiayu; Yang, Kun; et al.
ABSTRACT: The proper development of atrioventricular (AV) valves is critical for heart morphogenesis and for the formation of the cardiac conduction system. Defects in AV valve development are the most common type of congenital heart defect. Cardiac troponin I ( ctnni ), a structural and regulatory protein involved in cardiac muscle contraction, is a subunit of the troponin complex, but the functions and molecular mechanisms of ctnni during early heart development remain unclear. We created a knockout zebrafish model in which troponin I type 1b ( tnnilb ) ( Tnni‐HC, heart and craniofacial) was deleted using the clustered regularly interspaced short palindromic repeat/clustered regularly interspaced short palindromic repeat‐associated protein system. In the homozygous mutant, the embryos showed severe pericardial edema, malformation of the heart tube, reduction of heart rate without contraction and with almost no blood flow, heart cavity congestion, and lack of an endocardial ring or valve leaflet, resulting in 88.8 ± 6.0% lethality at 7 d postfertilization. Deletion of tnni1b caused the abnormal expression of several markers involved in AV valve development, including bmp4, cspg2, has2, notch1b, spp1, and Alcam. Myocardial re‐expression of tnni1b in mutants partially rescued the pericardial edema phenotype and AV canal (AVC) developmental defects. We further showed that tnni1b knockout in zebrafish and ctnni knockdown in rat h9c2 myocardial cells inhibited cardiac wnt signaling and that myocardial reactivation of wnt signaling partially rescued the abnormal expression of AVC markers caused by the tnnilb deletion. Taken together, our data suggest that tnni1b plays a vital role in zebrafish AV valve development by regulating the myocardial wnt signaling pathway.—Cai, C., Sang, C., Du, J., Jia, H., Tu, J., Wan, Q., Bao, B., Xie, S., Huang, Y., Li, A., Li, J., Yang, K., Wang, S., Lu, Q. Knockout of tnnilb in zebrafish causes defects in atrioventricular valve development via the inhibition of myocardial wnt signaling pathway. FASEB J. 33, 696–710 (2019). www.fasebj.org